Using Nematostella vectensis to Study the Interactions between Genome, Epigenome, and Bacteria in a Changing Environment - Fraune, Sebastian; Forêt, Sylvain; Reitzel, Adam M. (Frontiers in Marine Science, 2016)
The phenotype of an animal cannot be explained entirely by its genes. It is now clear that factors other than the genome contribute to the ecology and evolution of animals. Two fundamentally important factors are the associated microbiota and epigenetic regulations. Unlike the genes and regulatory regions of the genome, epigenetics and microbial composition can be rapidly modified, and may thus represent mechanisms for rapid acclimation to a changing environment. At present, the individual functions of epigenetics, microbiomes, and genomic mutations are largely studied in isolation, particularly for species in marine ecosystems. This single variable approach leaves significant questions open for how these mechanisms intersect in the acclimation and adaptation of organisms in different environments. Here, we propose that the starlet sea anemone, Nematostella vectensis, is a model of choice to investigate the complex interplay between adaptation as well as physiological and molecular plasticity in coastal ecosystems. N. vectensis’ geographic range spans four distinct coastlines, including a wide thermocline along the Atlantic coast of North America. N. vectensis is a particularly powerful invertebrate model for studying genome-environment interactions due to (1) the availability of a well-annotated genome, including preexisting data on genome methylation, histone modifications and miRNAs, (2) an extensive molecular toolkit including well-developed protocols for gene suppression and transgenesis, and (3) the simplicity of culture and experimentation in the laboratory. Taken together, N. vectensis has the tractability to connect the functional relationships between a host animal, microbes, and genome modifications to determine mechanisms underlying phenotypic plasticity and local adaptation.